Feasibility and Reliability of the System for Observing Play and Leisure Activity in Youth (SOPLAY) for Measuring Moderate to Vigorous Physical Activity in Children Visiting an Interactive Children's Museum Exhibition. Issue 1 (January 2018) - Agaronov, Alen; Leung, May May; Garcia, Jeanette M.; Kwan, Amy; Yeh, Ming-Chin; Zarcadoolas, Christina; Platkin, Charles S.
Purpose: To test the feasibility and reliability of a direct observation method for measuring moderate to vigorous physical activity (MVPA) in children visiting an interactive children's museum exhibition. Design: Direct observation was used to assess MVPA in children visiting an interactive children's museum exhibition on 2 weekend days in winter 2013. Setting: The Children's Museum of Manhattan's EatSleepPlay™: Building Health Every Day exhibition. Participants: Children (group level) visiting the museum exhibition. Measures: System for Observing Play and Leisure Activity in Youth (SOPLAY). Analyses: Interobserver reliability was analyzed for MVPA and activity type. Two-group analyses were conducted using a series of Wilcoxon rank sum tests. Results: A total of 545 children were observed over 288 observations. No significant differences were found between observers for MVPA ( r = .91, P = .6804) or activity type (κ = .90, P = .6334). Children participated in MVPA during 35.2% of all observations. No significant differences were found for participation in MVPA between boys (37.6%) and girls (32.8%, P = .1589). Conclusion: The SOPLAY may be a useful tool for measuring MVPA in interactive children's museum exhibitions. Research with multiple museum settings and diverse groups of children over longer periods of time is warranted to further establish the feasibility and reliability of the SOPLAY for measuring MVPA in this novel setting.